How character presence in advergames affects brand attitude and game performance: A cross‐cultural comparison. Issue 6 (21st October 2015) - Choi, Yung Kyun; Yoon, Sukki; Taylor, Charles R.
Abstract: Advertising within videogames has grown in importance over the last few years. This research investigates the impact of character presence in advergames on brand attitude and game performance, and how such effects depend on national culture. A total of 130 students participated in an experiment conducted in the US and Korea. Results show that when the featured brand in an advergame was a publicly consumed product, character's presence (vs. absence) had a positive effect on attitude toward the brand and gaming performance, but when the featured brand was a privately consumed product, character's presence had a negative effect on these variables. Furthermore, the emergence of the character–product interaction effect was dependent on national culture. Theoretical and practical implications are provided. Copyright © 2015 John Wiley & Sons, Ltd.